ALUMINO-MAGNESIOHULSITE, A NEW MEMBER OF THE HULSITE GROUP, IN KOTOITE MARBLE FROM EAST OF VERKHOYANSK, SAKHA-YAKUTIA, RUSSIA - Pertsev N.N.; Schreyer W.; Bernhardt H.-J.; Medenbach O.; Armbruster T. (My University, 2004)
Alumino-magnesiohulsite, the Al-and Mg-dominant analogue of hulsite, (Fe 2+ ,Mg) 2 (Fe 3+ ,Sn,Mg)O 2 BO 3 , is a new, optically spectacular mineral with pleochroism from brown to blue-green discovered in a magnesian skarn from northeastern Siberia. It forms prismatic, twinned crystals in a spinel-bearing kotoite marble at the contact of a Mesozoic granosyenite against Palaeozoic dolomite marbles. EMP analyses give: MgO 33.94; FeO 15.97; Al 2 O 3 15.86; SnO 2 11.88; TiO 2 0.75; MnO 0.42; CaO 0.11; B 2 O 3 (calc.) 17.07; total 96.00 wt.%, which can be recalculated to the formula (Mg 1.55 Fe 2+ 0.45) 2.00 (Al 0.63 Mg 0.17 Mn 0.01 Ti 0.02 Sn 0.16) 0.99 O 2 (BO 3). Optically, it is biaxial (+)about 1.78about 1.805, 2V z (measured from extinction data) = 33(5)°, is parallel to the prism axis b. Alumino-magnesiohulsite is monoclinic, space group P2/m, with a = 5.3344(7), b = 3.0300(5), c = 10.506(1) Å, = 94,46°, V = 169.29(4) Å 3 , Z = 2 and D calc = 3.84 g/cm 3 . Its cell parameters are significantly smaller than those of previously studied members of the hulsite group. A single-crystal X-ray study provided a pattern of cation distribution over the five distinct octahedral sites (M1-M5), which is not consistent with the formula given above. Despite this discrepany, the IMA-Commission on New Minerals and Mineral Names agreed for nomenclature and classification purposes with using the conventional stoichiometric formula in which the amount of R 2+ cations attributed to the tin-bearing unit equals that of the tetravalent ions, so that this attains an overall charge of 3.0 + . Taking into account variable tin contents as usual in hulsites, an ideal general formula of alumino-magnesiohulsite is Mg 2 (Al 1-2x Mg x Sn x)O 2 (BO 3) with x expected to be in the range 0.15-0.20. Alumino-magnesiohulsite occurs within bimineralic aggregates in the rock together with aluminous, tin-bearing ludwigite of the formula (Mg 1.62 Fe 2+ 0.38) (Fe 3+ 0.50 Al 0.31 Fe 2+ 0.07 Mn 0.01 Ca 0.01 Sn 0.05 Ti 0.05) O 2 (BO 3). These aggregates may be pseudomorphs after a pre-existing high-temperature mineral intermediate in composition between ludwigite and alumino-magnesiohulsite. The reason for the exceptionally high Al-content of the new hulsite-group mineral can only partly be due to its Al-saturation by coexisting spinel, because hulsites from other localities also coexisting with spinel contain much less Al.
Keywords: hulsite